Volumetric analysis of the damage and response of non-invasive brain stimulation in patients with spatial neglect after stroke: a subgroup analysis of the ELETRON trial - Januzzi, Mayara Apolinário [UNESP]; Luvizutto, G.J.; Miranda, Luana Aparecida [UNESP]; Silva, Taís Regina da [UNESP]; Winckler, Fernanda Cristina [UNESP]; Bazan, Silméia Garcia Zanati [UNESP]; Edwards, T.G.S.; Pontes-Neto, O.M.; Bazan, Rodrigo [UNESP]; Betting, Luiz Eduardo Gomes Garcia [UNESP] (My University, 2025)
This study aimed to analyze the compromised cortical and subcortical brain structures and quantify the volume of ischemic lesions in patients with hemispatial neglect after stroke treated with transcranial direct current stimulation (tDCS). This cross-sectional study was conducted using data from the ELETRON Trial. Computed tomography (CT) images of 23 patients who underwent anodal tDCS (A-tDCS), cathodal tDCS (C-tDCS), or placebo (sham-tDCS) were included. Lesion mapping based on high-resolution volumetric CT images was performed using an automated anatomical labeling atlas. The proportion of damage in each region and brain damage between groups were compared using chi-squared and Fisher's exact tests. The behavioral inattention test (BIT-C) score was significantly higher in the C-tDCS group than in sham-tDCS group (P=0.03). Gray matter analysis revealed that lesion extension in the A-tDCS group was 325.580 mm3, in C-tDCS was 231.700 mm3, and in the sham-tDCS was 241.574 mm3. The lesion extension in the white matter was 37.076 mm3 in the A-tDCS group, 22.258 mm3 in the C-tDCS group, and 40.556 mm3 in the sham-tDCS, all centered on the superior longitudinal fasciculus. Overall, the A-tDCS group presented with a larger lesion area in the gray matter than the C-tDCS group (P=0.046). The C-tDCS group showed a smaller proportion of areas with white matter damage than the A-tDCS (P=0.011) and S-tDCS (P=0.002) groups. Hemispatial neglect was significantly improved after C-tDCS; however, the extent of gray and white matter damage was smaller for this group.